Intergenerational mobility in a recession: Evidence from Sweden - Martin Nybom; Jan Stuhler (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
We use complete-count register data to describe various features of intergenerational mobility in Sweden. First, we document the extent of regional variation in educational and income mobility across Swedish municipalities, and describe its spatial pattern. Second, we study the stability of such regional rankings to the choice of mobility statistic. Third, we show that income inequality and mobility are negatively related, across all mobility measures. Fourth, we exploit variation in local exposure to show that the 1990s economic crisis and the 2007-2008 fi nancial crisis had a negative eff ect on income mobility.
Keywords: J62; R00; 330; The geography of intergenerational mobility; multigenerational mobility; income inequality; recession